JURIDICAL STUDY ON CRIMINAL ACTS OF ONLINE TOGEL GAMBLING - Gholib Yudha Mawaridi; Surya Nita; Eva Achjani Zulfa (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
Online gambling has gained popularity worldwide as a major entertainment industry. However, this growth has also brought about concerns regarding criminal activities such as fraud, money laundering, and illegal gambling operations. This study aims to analyze the considerations of judges in sentencing online gambling crimes and proving online togel gambling crimes. The research adopts a normative juridical approach (legal research) to examine the application of rules or norms in positive law using a statute-based approach. The analysis reveals that Article 303 and Article 303 Bis of the Criminal Code are utilized to address online gambling crimes, particularly online togel gambling. Although Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2011 regarding Electronic Information and Transactions can serve as a legal basis, it was not applied in this case. When deciding a criminal case, judges must take into account various factors, including ensuring that the actions charged meet the formulation of the offense and are in violation of the law, assessing the defendant's ability to be held accountable, and considering any justifications presented. Furthermore, the judge should also consider objective requirements, such as a complete indictment, case submission letter, and the case file. In the context of online togel gambling, evidence is evaluated using the theory of the Negative Legal System, which mandates at least two valid pieces of evidence as stipulated in Article 184 of the Criminal Procedure Code, in conjunction with the judge's own belief. Despite the availability of the Information and Electronic Transactions (ITE) Law as a legal basis, this study demonstrates the continued reliance on Article 303 of the Criminal Code for such cases, indicating that the principle of lex specialis derogat legi generali (specific laws override general laws) does not apply.